Vasomotor symptoms in menopause: a biomarker of cardiovascular disease risk and other chronic diseases?. (4th July 2017) - Biglia, N.; Cagnacci, A.; Gambacciani, M.; Lello, S.; Maffei, S.; Nappi, R. E.
Abstract: Menopausal disorders may include shorter-term symptoms, such as hot flushes and night sweats (vasomotor symptoms, VMS) and longer-term chronic conditions such as cardiovascular disease (CVD), osteoporosis, and cognitive impairment. Initially, no clear link between the shorter-term symptoms and longer-term chronic conditions was evident and these disorders seemed to occur independently from each other. However, there is a growing body of evidence demonstrating that VMS may be a biomarker for chronic disease. In this review, the association between VMS and a range of chronic postmenopausal conditions including CVD, osteoporosis, and cognitive decline is discussed. Prevention of CVD in women, as for men, should be started early, and effective management of chronic disease in postmenopausal women has to start with the awareness that VMS during menopause are harbingers of things to come and should be treated accordingly.